Pengaruh Model Pembelaaran REACT terhadap Hasil Belajar Geografi Siswa Kelas XI IPS MAN 2 Kota Padang - Hasanah, Niswatun; Anwar, Syafri (TSAQOFAH, 2024)
This research discusses the influence of the REACT learning model on the geography learning outcomes of class XI IPS MAN 2 Padang City students. This research aims to determine: 1) Geography learning outcomes after using the REACT learning model. 2) Implementation of learning using the REACT learning model. 3) The influence of the REACT learning model on learning outcomes. Quasi Experimental Design research design type Pre-Test and Post-Test with Non-Equivalent Control-Group Design. The data collection technique uses a written test consisting of 25 Multiple Choice (PG) questions. The data analysis technique uses an independent samples test. The research results showed that the results of learning geography using the REACT learning model in the experimental class were higher than those in the control class which did not apply the REACT learning model. These results are supported by the results of the independent samples test, obtained tcount > ttable, namely 2.866 > 1.667.